ACCOMPANIMENT / LEGAL ASSISTANCE OF BUSINESS LICENSING OF NOSTALGIA COFFEESHOP THROUGH OSS SYSTEM - Excel Brayen Sandoval; Lu Sudirman (ConCEPt - Conference on Community Engagement Project, 2022)
After the enactment of Law no. 11 of 2020 concerning Job Creation, as has been followed up with PP No. 7 of 2021 concerning the Ease, Protection, and Empowerment of Cooperatives and Micro, Small, and Medium Enterprises, it has been regulated that "The Business Registration Number is valid as a single license, and is valid as identity and legality in carrying out business activities." With this legality, business actors can carry out their business activities with legal guarantees and certainty as regulated by applicable laws and regulations. The Nostalgia Coffee Shop Micro Business, which is owned by Barly Fahmi, does not yet have the NIB as referred to previously, therefore a socialization is needed in order to provide understanding to business actors, especially the owners of Nostalgia Coffee Shop in terms of the importance of business legality to provide legal guarantees and certainty for the implementation of a business. business activities. After conducting socialization, the author offers assistance in managing business legality in the form of NIB for Nostalgia Coffee Shop business actors, namely by submitting a PkM proposal and a guide to registering access rights for micro and small businesses on the OSS.go.id page. After being approved, the author provides assistance in managing the legality of the Nostalgia Coffee Shop micro business, namely by interviewing, observing and documenting methods.